Peripheral Nerve Field Stimulation for the Management of Localized Chronic Intractable Back Pain: Results From a Randomized Controlled Study. Issue 6 (11th April 2013) - McRoberts, W. Porter; Wolkowitz, Richard; Meyer, D Joseph; Lipov, Eugene; Joshi, Jay; Davis, Bennet; Cairns, Kevin D.; Barolat, Giancarlo
<x xml:space="preserve">Abstract</x> Objectives Improved device technology has caused a renewed interest in peripheral nerve field stimulation (PNfS). This study sought to obtain preliminary estimates of the safety and efficacy of PNfS in patients with localized chronic intractable pain of the back. Materials and Methods This Institutional Review Board‐approved, prospective, randomized, controlled, crossover study consisted of two phases. During phase I, patients rotated through four stimulation groups (minimal, subthreshold, low frequency, and standard stimulation). If a 50% reduction in pain was achieved during any of the three active stimulation groups (responder), the patient proceeded to phase II, which began with implant of the permanent system and lasted 52 weeks. The primary endpoint was a reduction in pain, assessed by the visual analog scale (VAS). Analysis of variance, including the effects of patient, treatment, and study period, was used for phase I results. Phase II results were analyzed by paired t‐tests. Results A total of 44 patients were enrolled at five sites. Of these patients, 32 were implanted with a trial system and 30 completed phase I. During phase I, there were significant differences in mean VAS scores between minimal stimulation and subthreshold stimulation (p = 0.003), low frequency stimulation (p < 0.001), and standard stimulation (p < 0.001). Twenty‐four patients were classified as responders to the therapy, and 23 patients received permanent system placement. Significant differences in VAS scores were observed between baseline and all follow‐up visits during phase II (p < 0.001) Conclusions The results provide evidence to support safety and effectiveness of PNfS as an aid in the management of chronic, localized back pain.